The Values of Aqidah and Akhlak in the Book Mukhtasar ‘Abdillah Al-Harari Al-Kafil Bi ‘Ilm Ad-Din Ad-Daruri by Sheikh ‘Abdillah Al-Harari - Isma Gunawan; Tuti Alawiyah; Habibullah Habibullah (Fakultas Agama Islam, 2026)
This study aims to analyze the values of religious belief and moral education contained in the book Mukhtasar ‘Abdillah Al-Harariy Al-Kafil bi ‘Ilm Ad-Din Adh-Dharuriy by Sheikh Abdullah Al-Harariy, as well as their relevance to contemporary Islamic education. The study employs a qualitative approach using the library research method. Primary data sources come from the book Mukhtasar ‘Abdillah Al-Harariy Al-Kafil bi ‘Ilm Ad-Din Adh-Dharuriy, while secondary data are obtained from books, scientific journals, theses, and various literature relevant to the research theme. Data analysis was conducted using content analysis to identify and interpret the educational values contained in the book. The research findings indicate that this book contains fundamental doctrinal values, including an understanding of the two testimonies of faith (shahadah), the pillars of faith (rukun al-iman), the attributes of Allah, and the principles of tawhid in accordance with the teachings of Ahlus Sunnah wal Jama‘ah. Furthermore, the book emphasizes the importance of cultivating noble character (akhlakul karimah) in one’s relationship with Allah, fellow human beings, and the environment. The values contained within it are highly relevant to the current needs of Islamic education, particularly in strengthening faith, shaping religious character, and shielding the younger generation from various moral and ideological challenges in the modern era. Therefore, this book is worthy of being used as a reference in the education of faith and moral character.